A Conceptual Design for Knowledge Management System 2.0 Based on Soft Systems Methodology (SSM) Approach - Mina Feili; Roohollah Tavallaei (فرایند مدیریت و توسعه, 2022)
Purpose: With the emergence of new approaches in knowledge management, the need to use new tools in the knowledge management of organizations is imperative. The main purpose of this research is to design a conceptual model of knowledge management system 2.0 in Hajj and Pilgrimage Organization applying the methodology of soft systems. Methodology: The type of this research was exploratory and the data collection methods included field study, interviews, as well as descriptive and analytical questionnaires. Data collected through these methods were used to implement the seven steps of soft systems methodology. The statistical population was composed of managers and senior experts of Hajj and Pilgrimage Organization, who had full knowledge of the structure of the organization and the subjects of knowledge management and information technologies. Findings: Based on the research findings, the main components of knowledge management system 2.0 consist of cooperation, collaboration, connection, dialogue, training, motivational incentives, managerial stability, system certainty and encouragement/punishment. Among these nine components, the most important one in the organization is cooperation, which should be expanded among employees, and all units of the organization. The enhancement of cooperation calls for supporting cooperative attitude in the organization by senior management. Implications: It is suggested that participatory activity and a sense of atmosphere be expanded in the organization so that employees may know that their views affect the development of the organization. It is also suggested that balance be made among materialistic issues, like-mindedness and unison in the organization.